Prenatal Diagnosis of Agenesis of Ductus Venosus: A Retrospective Study of Anatomic Variants, Associated Anomalies and Impact on Postnatal Outcome - Strizek, Brigitte; Zamprakou, Aikaterini; Gottschalk, Ingo; Roethlisberger, Maria; Hellmund, Astrid; Müller, Andreas; Gembruch, Ulrich; Geipel, Annegret; Berg, Christoph (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Purpose To assess the anatomic variants, associated anomalies and postnatal outcome of fetuses with a prenatally diagnosed agenesis of ductus venosus (ADV).Materials and Methods Retrospective study of 119 cases with agenesis of ductus venosus diagnosed by prenatal ultrasound in two tertiary referral centers from 2006 to 2014. The type and location of the umbilical venous drainage site was noted. Charts were reviewed for associated structural or chromosomal anomalies, pregnancy outcome and postnatal course.Results In 24 cases (20.2 %) ADV was an isolated finding, while 95 cases (79.8 %) had associated anomalies. We identified 84 cases (70.6 %) with intrahepatic and 35 cases (29.4 %) with extrahepatic drainage of the umbilical vein. 58.8 % of neonates were alive at follow-up. There was no statistical association between drainage site and associated anomalies or outcome. Postnatal outcome was determined by the presence and severity of associated anomalies. There was no adverse outcome in the isolated group related to ADV. Overall, there were 6 persistent portosystemic shunts, 3 of them with a spontaneous closure, and one total agenesis of the portal venous system with lethal outcome.Conclusion Postnatal outcome in cases with ADV mainly depends on the presence of associated anomalies. In isolated cases the prognosis is generally good, but neonates with a prenatally diagnosed portosystemic shunt should be followed until its occlusion. Portal venous system agenesis is rare but should be ruled out on prenatal ultrasound.
Keywords: portosystemic shunt; intrahepatic drainage; extrahepatic drainage; outcome; ductus venosus agenesis